My little pony friendship is magic. Pony trick or treat [videorecording (DVD)]. (Shout! Factory, 2018)
It's time for tricks and treats in this My Pony Halloween release. Favorite legends are told on a camping trip, the changelings return, 'zombie,' ponies crave cookies and Twilight and her friends must rescue an ancient wizard from the Pony Shadows.